2018
DOI: 10.1177/1468087418819527
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of spray collapse in multi-hole gasoline direct-injection fuel injectors

Abstract: A parametric study was conducted to predict the conditions leading to spray collapse in multi-hole gasoline direct-injection fuel injectors using computational fluid dynamics simulations. The computational fluid dynamics simulations were performed using an in-house multi-dimensional code that accounts for thermal non-equilibrium and entrainment of the non-condensable gas and coupled with primary atomization. The simulations were performed for a fixed injection pressure and fuel temperature on nine different si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…As a consequence, reduced axial liquid penetration values are expected for both cases, 47,48 along with a strong collapse of the spray jet. 41,49 The low threshold axial liquid penetration provided by Sandia was the only relevant experimental measurement available for the validation of the G4 condition. Still, during the ECN6 Workshop, it was suggested by Sandia that such data could also be used as a reference for investigating the axial vapor penetration.…”
Section: Late Injection Spray G4 and Spray G7 Conditionsmentioning
confidence: 99%
“…As a consequence, reduced axial liquid penetration values are expected for both cases, 47,48 along with a strong collapse of the spray jet. 41,49 The low threshold axial liquid penetration provided by Sandia was the only relevant experimental measurement available for the validation of the G4 condition. Still, during the ECN6 Workshop, it was suggested by Sandia that such data could also be used as a reference for investigating the axial vapor penetration.…”
Section: Late Injection Spray G4 and Spray G7 Conditionsmentioning
confidence: 99%
“…Subsequent expansion of these vapor bubbles due to rapid decompression during the injection process causes catastrophic disintegration of the liquid jet and resulting in finer droplet size distribution. [28][29][30][31][32][33] This unique quality of flash boiling sprays is very important for homogeneous mixture formation. Experimental studies using single hole injector showed that under flash boiling conditions, liquid penetration length reduces compared to normal fuel temperature cases.…”
Section: Introductionmentioning
confidence: 99%
“…The injection pressure is the main driver that initially pushes the spray inside the chamber allowing for the liquid spray to penetrate at early injection timings. Previous analyses of the mixture formation process in the Spray G conditions 13,[32][33][34][35] have shown that during injection, a strong aerodynamic motion is generated by air entrainment which persists after the end of injection. This motion becomes the main driver for the propagation of the vaporized fuel jet.…”
Section: Analysis Of the Aerodynamic Mechanism Leading To The Componementioning
confidence: 99%